2019
DOI: 10.1371/journal.pone.0215822
|View full text |Cite
|
Sign up to set email alerts
|

Consensus and variations in cell line specificity among human metapneumovirus strains

Abstract: Human metapneumovirus (HMPV) has been a notable etiological agent of acute respiratory infection in humans, but it was not discovered until 2001, because HMPV replicates only in a limited number of cell lines and the cytopathic effect (CPE) is often mild. To promote the study of HMPV, several groups have generated green fluorescent protein (GFP)-expressing recombinant HMPV strains (HMPV GFP ). However, the growing evidence has complicated the understanding of cell line specificity of HMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 76 publications
(115 reference statements)
1
48
0
Order By: Relevance
“…In that regard, many HMPV subtypes co-circulate each year with high genetic diversity among A and B subtypes, particularly in the case of the less conserved G and SH proteins, with approximately 37% and 59% amino acid sequence homologies between subtypes, respectively [9,14]. In parallel, we and others previously demonstrated that HMPV viruses diverge in their in vitro and/or in vivo phenotypes in a strain-dependent manner, notably by considering the HMPV F and G proteins and their functions [18,[29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 62%
“…In that regard, many HMPV subtypes co-circulate each year with high genetic diversity among A and B subtypes, particularly in the case of the less conserved G and SH proteins, with approximately 37% and 59% amino acid sequence homologies between subtypes, respectively [9,14]. In parallel, we and others previously demonstrated that HMPV viruses diverge in their in vitro and/or in vivo phenotypes in a strain-dependent manner, notably by considering the HMPV F and G proteins and their functions [18,[29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 62%
“…Human epithelial colorectal adenocarcarcinoma cells (Caco-2) and human lung cancer cells (Calu-3) were maintained in DMEM, 20% FCS, 1% NEAA, 1% P/S. VeroE6/TMPRSS2 cells were obtained from the Centre for AIDS Reagents (National Institute for Biological Standards and Control) (Matsuyama et al, 2020; Nao et al, 2019), and maintained in DMEM, 10% FCS, 1% NEAA, 1% P/S, 1 mg/ml Geneticin (G418). Air liquid interface Human airway epithelial cells (HAEs) were purchased from Epithelix and maintained in Mucilair cell culture medium (Epithelix).…”
Section: Methodsmentioning
confidence: 99%
“…SARS-CoV-2 (JPN/TY/WK-521 strain) and VeroE6/TMPRSS2 cells [ 13 ] were obtained from the National Institute of Infectious Diseases (Tokyo, Japan). VeroE6/TMPRSS2 cells were inoculated with SARS-CoV-2 and then cultured in virus growth medium containing Dulbecco’s modified Eagle’s medium (Nissui Pharmaceutical Co., Ltd., Tokyo, Japan) supplemented with 1% fetal bovine serum (FBS), 20 mM l -glutamine (Wako Pure Chemical Industries, Ltd., Osaka, Japan), and 100 μg/mL of kanamycin (Meiji Seika Pharma Co., Ltd., Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%